No significant relationship found between spontaneous motor tempo, heartbeat, and individual alpha frequency: an analysis of internal tempos - Tamaka Harada; Giovanna Mioni; Nicola Cellini; Yuko Yotsumoto (Scientific Reports)
Abstract Many theories of time perception propose the existence of an internal pacemaker, and studies across behavioral, physiological, and neuroscience fields have explored this concept. Specifically, Spontaneous Motor Tempo (SMT), the most comfortable and natural tapping tempo for each individual, is thought to reflect this internal pacemaker’s tempo. Changes in heart rate are also linked to time estimation, while Individual Alpha Frequency (IAF), the peak in the alpha range (8–13 Hz) observed in EEG, is reported to reflect the brain’s temporal processing. Despite the associations of SMT, heart rate, and IAF with intrinsic tempo, their interrelations remain unexplored. In this pre-registered study, we measured SMT, IAF, and heart rate in 32 healthy university students aged 18–21 and examined how these variables relate to each other. During the experiment, participants sat with their eyes closed for 5 min while we recorded their EEG and heart rate. They then tapped the space key with their index finger at their most comfortable tempo, which we used to determine SMT. Participants also completed a questionnaire about their age, chronotype, and musical experience. Our results showed no significant correlations among SMT, heart rate, and IAF. Regression analysis further confirmed that SMT is not influenced by heart rate or IAF. Therefore, no significant relationships among behavioral, physiological, and neuroscience-related tempo were uncovered. Our contribution lies in measuring SMT, heart rate, and IAF within the same experimental context. All procedures, including scripts used for the analyses, were pre-registered before data collection, and we report these null results to mitigate publication bias.